Penerapan Metode Waterfall Dalam Perancangan Sistem Informasi Akuntansi Pengiriman Barang - Anna Anna; Nurmalasari Nurmalasari; Yayuk Rohayani (LPPM Universitas Bina Sarana Informatika, 2020)
Freight Forwarding services are activities in the economy that create economic value. Delivery of goods occurs because of a sale and purchase of goods transaction, where every item sold will be sent to the buyer using the goods delivery service. With the service of shipping goods make it easy for customers to send goods, important documents and so on at a lower cost. PT. Suryagita Nusaraya is a company focused on moving goods delivery services, with the aim of shipping goods in various cities throughout Indonesia. However, PT. Suryagita Nusaraya still uses paper media to record data such as customer data,transaction data, tariff data, and financial reporting. This requires a long time and delay in finding the data needed and allows errors in making transaction reports. So the company requires the existence of an information system that supports and provides satisfying services for customers. For that reason, the writer tries to make an Accounting Information System for Shipping Services at PT. Suryagita Nusaraya Website based. This can be a solution for companies in developing goods delivery services with a computerized system so as to facilitate the activities of the company.